Zinc Gallate Nanoplates on Microporous Organic Hollow Nanoplatforms for Enhanced Reductive CO2 Fixation to Formamides - Kim, Hyun Su; Jang, June Young; Ko, Yoon Joo; Jang, Hye Young; Son, Seung Uk (ACS Applied Nano Materials, 2024)
This work suggests an engineering methodology for catalytic 2D materials to achieve more efficient catalytic systems. Zinc gallate (ZnG), a Lewis acidic material with a thin 2D morphology, can easily form aggregates through layer-layer packing. Inner parts of ZnG aggregates would have difficulty in interacting with substrates. By coating hollow microporous organic polymer (H-MOP) supports with ZnG, the catalytic performance of ZnG can be enhanced due to facilitated contact of substrates with Zn species in shells. H-MOP@ZnG-2 with an optimal ZnG coating showed a much enhanced catalytic performance for the reductive carbon dioxide fixation with amines to formamides compared with ZnG. Various amines can be utilized in the reductive carbon dioxide fixation to formamides. In addition, H-MOP@ZnG-2 showed recyclability, maintaining its catalytic performance for five successive reactions.
Keywords: Carbon dioxide fixation; Catalytic performance; Formamides; Hollow materials; Microporous; Microporous organic polymers; Nano-catalyst; Nanoplates; Organics; Zinc gallate; carbon dioxide; hollow material; microporous organic polymer; nanocatalyst; nanoplate; zinc